2017
DOI: 10.1371/journal.pone.0173894
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 genetic diversity and antiretroviral drug resistance among individuals from Roraima state, northern Brazil

Abstract: The HIV-1 epidemic in Brazil has spread towards the Northern country region, but little is known about HIV-1 subtypes and prevalence of HIV strains with resistance mutations to antiretrovirals in some of the Northern states. HIV-1 protease (PR) and reverse transcriptase (RT) sequences were obtained from 73 treatment-naive and -experienced subjects followed between 2013 and 2014 at a public health reference unit from Roraima, the northernmost Brazilian state. The most prevalent HIV-1 clade observed in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…This was consistent with other data from Brazil [12][13][14][15][16][17][18][19][20] with the exception of the southern states, where subtype C has been found to prevail. 21 To a lesser extent, presence of recombinant forms between subtypes B and F, K and between F and subtype F1 was also found.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This was consistent with other data from Brazil [12][13][14][15][16][17][18][19][20] with the exception of the southern states, where subtype C has been found to prevail. 21 To a lesser extent, presence of recombinant forms between subtypes B and F, K and between F and subtype F1 was also found.…”
Section: Discussionsupporting
confidence: 93%
“…Subtype C was not observed in the samples, but the prevalence of this subtype is increasing in Brazil, 22 apparently with disease progression characteristics differing from those of subtype B. 23 Subtype F is the second most common form in the cities of Santos 24,25 and Rio de Janeiro 18 and in the states of Minas 12,13,16,17,25,27 Ferreira et al 22 found that the prevalence of transmitted drug resistance in São Paulo and Campinas was 7.6% and that 76.0% of these cases carried mutations for resistance to NNRTIs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Different rates of TDR to the main ARV drug classes nucleoside and nonnucleoside reverse transcriptase inhibitors (NRTI and NNRTI, respectively) and protease inhibitors (PI) have been reported in Brazil, mostly ranging from 5% to 15% . In Northern Brazil, TDR rates ranging from 0% to 21% have been reported; however, studies from this region are still scarce …”
mentioning
confidence: 99%
“…The higher prevalence of recombinant forms when compared to recent Brazilian Sanger sequencing-based studies (ranging from 5 to 16%) can be attributed to the smaller genomic region analyzed in the latter, mostly based only on pol gene, which impairs the accurate classification of recombinants (Librelotto et al, 2015; Moura et al, 2015; da Costa et al, 2016; Dos Anjos Silva et al, 2016; Delatorre et al, 2017; Filho and Brites, 2017; Lima et al, 2017). Some of these studies covering small genomic regions could not find recombinant strains, like the study conducted by Corado et al (2017) among 73 individuals from Roraima state, northern Brazil. A study conducted by Graf et al (2016) found a higher proportion of recombinant strains than others Sanger-based studies (21%, 66/317).…”
Section: Discussionmentioning
confidence: 99%